Leadership, power and, organizational mobilization (2013)
The objective of this study is to analyze the leadership and power processes as emerging phenomena that occur within organizations due to interactions between the people (agents) that belong to the organization. It is assumed that the organization is a dynamic system in continuous changing process that mobilizes the firm by virtue of its dynamic relationships between leaders and employees. As this is a theoretical study, the analysis is supported by a review of the literature. In conclusion it affirms that leadership and power can mobilize the organization and can lead to productive imbalances, which promote organizational development and sustainability. © 2013 Universidad ICESI. Published by Elsevier España. All rights reserved.